Maternal Nationality, Migration-Related Health Inequalities, and Pregnancy Complications in Cyprus: A Retrospective Analysis of Routinely Collected Maternity Records - Paschalis Matzinos; Lenos Mastrou; Alexandros Heraclides; Demetris Lamnisos; Konstantinos Giannakou (Journal of Immigrant and Minority Health, 2026)
Abstract Increasing international migration has transformed the maternity population of Cyprus, yet little is known about whether maternal health profiles and pregnancy complications differ across nationality groups. Understanding such differences is important for identifying potential maternal health inequalities and informing equitable maternity care in increasingly diverse maternity populations. This retrospective study analysed routinely collected maternity records from Paphos General Hospital, Cyprus. Of 2,233 deliveries between 2015 and 2020, medical records could be retrieved and contained sufficient information for abstraction for 1,112 births (49.8%). The unit of analysis was the birth. Maternal nationality as recorded at hospital registration was used as a proxy measure of migration-related characteristics and classified into seven categories. Pre-existing maternal conditions and pregnancy complications, gestational diabetes mellitus (GDM), gestational hypertension, preeclampsia and fetal growth restriction, were compared using Fisher’s exact and Kruskal–Wallis tests, with Cramér’s V (V) reported as an effect-size measure. Logistic regression, including Firth’s penalized regression for sparse outcomes, estimated crude and adjusted associations controlling for maternal age, parity, smoking, educational level and any pre-existing chronic condition. Among 1,112 births, maternal age, parity, smoking and educational level differed markedly across nationality categories (all p < 0.001), with the largest effect sizes observed for smoking (V = 0.35) and educational level (V = 0.33). Crude GDM prevalence ranged from 13.8% among women from the Middle East and North Africa (MENA) to 41.2% among women from Sub-Saharan Africa ( p = 0.019; V = 0.12). After adjustment, MENA nationality was associated with lower odds of GDM (adjusted odds ratio 0.53, 95% CI 0.30–0.95, p = 0.032); this was the only statistically significant adjusted association among 24 nationality comparisons and should therefore be interpreted cautiously in the context of multiple testing. No statistically significant adjusted association was detected for gestational hypertension, preeclampsia or fetal growth restriction, with Cramér’s V ranging from 0.03 to 0.09 for these complications. Births to women of different nationalities showed marked variation in sociodemographic and pre-existing health profiles, while estimates for several pregnancy complications remained imprecise, particularly in the smaller nationality categories. Lower adjusted odds of GDM among MENA women, a predominantly Syrian population, were robust to three sensitivity analyses; the institutional screening protocol was universal and remained unchanged throughout the study period, although individual screening completion could not be assessed systematically. The study was underpowered for the rarer outcomes, was not designed as an equivalence analysis, and measured no aspect of maternity-care delivery, so it cannot determine whether care provision contributed to the pattern observed.